Cervical Myelopathy as the Most Common Symptoms in Patients Undergoing C-Spine Surgery in the Spine Division, Department of Neurosurgery, Cipto Mangunkusumo General Hospital, from January 2012 to December 2016 - Mohamad Saekhu; Jeremia Prasetya Pardede; Renindra Ananda Aman; Syaiful Ichwan; Wismaji Sadewo; Samsul Ashari; Setyowidi Nugroho (Neurologico Spinale Medico Chirurgico, 2018)
Background: Cervical spine disease has the potential to reduce productivity in aﬀected patients because of myelopathy and mood disorder (e.g. depression) which lead to decreasing of the patient’s quality of life.Objective: This study aims to elaborate on the most frequent symptoms and pathology of C-spine disease in patients who underwent a surgical procedure over the period time from January 2012 to December 2016.Method: This study is a retrospective. All patients who underwent surgery for the C-spine disease are included. The data was obtained from the records in our spine database.Result: The total number of surgical procedures for spine disease over the 5 years was 345 procedures, with 127 procedures in the C-spine which are the second most common procedures of spine surgery in Department of Neurosurgery FMUI. The C-spine diseases were more common in males, aged more than 50 years old. The most frequent disease or pathology is a degenerative disease, and yet, tumour cases show an increasing number and became the most common pathology in the year of 2016. The most common procedure is anterior cervicaldiscectomy and fusion (ACDF).Conclusion: Our study showed that the most common symptoms and pathology are myelopathies and degenerative disease respectively, which has similarity with another study in the term of the mostfrequent pathology and surgical procedure. The finding of the more advanced neurological condition by the time of surgery as the most common symptom is found to be contradictory with other studies in western countries.